Implementasi Sistem Among melalui Model Pembelajaran PBL pada Pendidikan Pancasila Kelas X PM 3 - Ainul Siti Fatimah; Supriyono Purwosaputro; Puput Tri Hartanti (Departement of Mathematics Education, 2024)
This research aims to describe the implementation of the among system KHD through the Problem Based Learning learning model in Pancasila Education subjects. This research will be carried out in Class X PM 3 SMK Negeri 2 Semarang with the material